GUIDELINES FOR THE PROMOTION OF HONESTY FOR YOUTH IN RANONG PROVINCE - chayanon, sunthan (วารสาร มจร พุทธปัญญาปริทรรศน์, 2023)
The research on Guidelines for the Promotion of Honesty for Youth in Ranong Province is aimed to 1) study the current situation regarding honesty in the Thai context, and 2) provide guidelines for the promotion of honesty for youth in Ranong province. This is a type of qualitative research in which the researcher reviewed the related documents, conducted in-depth interviews, made observations, and organized a focus group discussion. The obtained data were analyzed using content analysis, categorized into groups for interpretation and presentation, and verified by triangulation method. The results indicated that: 1) honesty is a basic righteousness among good Samaritans, involving holding on to what is right, behaving truthfully towards oneself and others, avoiding fraudulence, maintaining transparency in work, and being verifiable, and 2) guidelines for promoting honesty use the FRA model, which includes: (1) family, (2) appreciation of religion, and (3) attitude towards honesty.